2008
DOI: 10.1105/tpc.108.058826
|View full text |Cite
|
Sign up to set email alerts
|

ArabidopsisPhosphatidylinositol-4-Monophosphate 5-Kinase 4 Regulates Pollen Tube Growth and Polarity by Modulating Membrane Recycling

Abstract: Phosphatidylinositol-4-monophosphate 5-kinases produce phosphatidylinositol (4,5)-bisphosphate [PtdIns(4,5)P 2 ] and have been implicated in vesicle trafficking and cytoskeletal rearrangements. Here, we adopted a reverse genetics approach to investigate the function of the Arabidopsis thaliana pollen-expressed gene encoding phosphatidylinositol-4-monophosphate 5-kinase 4 (PIP5K4). Pollen germination, tube growth, and polarity were significantly impaired in homozygous mutant plants lacking PIP5K4 transcript. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

26
205
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 148 publications
(231 citation statements)
references
References 53 publications
26
205
0
Order By: Relevance
“…As shown in Figure 2D (right panel), when supplemented with exogenous PtdIns(4,5)P 2 , the pip5k2 seedlings could produce as many lateral roots as WT seedlings, while treatment with PtdIns4P or carrier only (which is used to transfer the lipid into plant cells [22,54]) had no effect. This indicates that the reduced lateral root formation of pip5k2 is indeed caused by insufficient endogenous PtdIns(4,5)P 2 production.…”
Section: Pip5k2 Knockout Results In Reduced Lateral Root Formationmentioning
confidence: 98%
See 1 more Smart Citation
“…As shown in Figure 2D (right panel), when supplemented with exogenous PtdIns(4,5)P 2 , the pip5k2 seedlings could produce as many lateral roots as WT seedlings, while treatment with PtdIns4P or carrier only (which is used to transfer the lipid into plant cells [22,54]) had no effect. This indicates that the reduced lateral root formation of pip5k2 is indeed caused by insufficient endogenous PtdIns(4,5)P 2 production.…”
Section: Pip5k2 Knockout Results In Reduced Lateral Root Formationmentioning
confidence: 98%
“…The catalytic activities of using PtdIns4P as the preferred substrate to generate PtdIns(4,5)P 2 have all been characterized [15][16][17][18]. Studies have revealed the physiological functions of some PIP5Ks, including PIP5K1 in abscisic acid signaling [19]; PIP5K3 in root hair formation and growth [16,20]; PIP5K4 in stomata opening [21]; and PIP5K4-6 in pollen tube growth [17,22]. In addition, PIP5K9 regulates root growth and is involved in sugar signaling [23].…”
Section: Introductionmentioning
confidence: 99%
“…However, in terms of enzymatic activity, plant type I/II PIPKs resemble animal type I PIPKs, with a lack of activity toward the PtdIns5P found in animal type II PIPKs. In contrast to the structural and biochemical characteristics, little is known about the function of plant type I/II PIPKs in physiological processes; AtPIP5K3 regulates tip growth of root hairs (Kusano et al, 2008;Stenzel et al, 2008), whereas AtPIP5K4 and AtPIP5K5 are involved in apical growth of pollen tubes Sousa et al, 2008). In P. patens PIPKs, although the functions of PpPIPKs are not clear, it is likely that PpPIPK1 and PpPIPK2 are functionally distinct because of the unique enzymatic activity of PpPIPK2 as a PtdIns kinase (Saavedra et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the establishment of the roles of PIPKs in polarized tip growth of root hairs and pollen tubes via their localization at plasma membranes in Arabidopsis Kusano et al, 2008;Sousa et al, 2008;Stenzel et al, 2008), the regulatory mode of this plasma membrane localization remains elusive in plants. Here, we identified a dibasic amino acid pair, KR, in the activation loop of PpPIPK1, the biological relevance of which is 2-fold.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation